Mechanistic Features in Al(I)-Mediated Oxidative Addition of Aryl C–F Bonds: Insights From Density Functional Theory Calculations - Zhang, Xiangfei; Li, Ping; Wang, Binju; Cao, Zexing (Frontiers in Chemistry, 2019)
The oxidative addition of a range of robust aryl C–F bonds to a single Al(I) center supported by a (NacNac)− bidentate ligand ((NacNac)− = [ArNC(Me)CHC(Me)NAr]− and Ar = 2,6–Pr2iC6H3) have been explored by density functional theory calculations. Our calculations demonstrate that the Al(I) center-mediated C–F insertion generally proceeds via the concerted mechanism that involve both the donation (nAl→σC-F*) and back-donation (σF(p)→πAl(p)*) interactions. In addition, the predicted free energy barriers for the C–F bond activation show good agreement with the experimental information available. Finally, the comparative studies show that B(I) is the most active among group III metals (B, Al, Ga), thus supplying a testable prediction for experiments.